2019
DOI: 10.1186/s12879-019-3889-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient-related factors, antibiotic prescribing and antimicrobial resistance of the commensal Staphylococcus aureus and Streptococcus pneumoniae in a healthy population - Hungarian results of the APRES study

Abstract: BackgroundAntimicrobial resistance (AMR) is an increasing public health problem worldwide.We studied some patient-related factors that might influence the antimicrobial resistance.and whether the volume of antibiotic prescribing of the primary care physicians correlate with the antibiotic resistance rates of commensal nasal Staphylococcus aureus and Streptococcus pneumoniae.MethodsThe socio-demographic questionnaires, the antibiotic prescription and resistance data of commensal nasal S. aureus and S. pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
(29 reference statements)
0
9
0
2
Order By: Relevance
“…Antibiotics can save the life of an infected person if used appropriately, but they are among the most widely inappropriately used medicines in the world, especially in low-and middle-income countries. 1 This has led to the development of serious microbial resistance, [2][3][4] which has become a major public health concern. Antimicrobial resistance (AMR) occurs when antibiotics are no longer able to kill bacteria as they should.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics can save the life of an infected person if used appropriately, but they are among the most widely inappropriately used medicines in the world, especially in low-and middle-income countries. 1 This has led to the development of serious microbial resistance, [2][3][4] which has become a major public health concern. Antimicrobial resistance (AMR) occurs when antibiotics are no longer able to kill bacteria as they should.…”
Section: Introductionmentioning
confidence: 99%
“…reported that age was significantly associated with resistance to antibiotics [ 7 ]. However other studies have reported that age is not a factor in determining antibiotic resistance in patients with febrile UTI specifically, or in patients generally [ 8 , 9 ]. An Iranian study also found no significant association between age and the likelihood of having extended-spectrum beta-lactamase (ESBL)-producing bacteria [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lebanon [17] reported that the frequency of antibiotic resistance was 53.7% (39.9% were multidrugresistant), and different kinds of pathogenic bacteria that were resistant to different kinds of antibiotics, such as Escherichia coli strains, were mostly susceptible to carbapenems and tigecycline, while Klebsiella species were mostly susceptible to amikacin and carbapenems. Moreover, a study in Hungary showed that the frequency of prescriptions from clinicians was related to the percentage of antibiotic resistance [18]. In addition, a prospective cohort study demonstrated that several bacterial pathogenic species were resistant to different kinds of antibiotics in the United Kingdom; 43.0% of patients with E. coli were resistant to at least one antibiotic, with the highest resistance to amoxicillin [19].…”
Section: Discussionmentioning
confidence: 99%